2021
DOI: 10.3390/su13105711
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Its Related Factors during the First COVID-19 Lockdown in Germany

Abstract: Lockdown measures including the closure of physical activity facilities were installed against the spread of the novel coronavirus in March 2020. The aim of the current online survey was to assess the lockdown effects on physical activity in German adults. We assessed physical activity using the European Health Interview Survey (EHIS) questionnaire. Pre-lockdown vs. lockdown differences were tested with the Χ2 test and the Student’s t-test for paired data. Predictor variables to explain compliance with physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 41 publications
5
22
0
1
Order By: Relevance
“…Given these results, findings from the first wave of the pandemic and the ensuing lockdowns are alarming. Numerous studies worldwide and in Germany have documented reduced PA at the level of overall samples [10][11][12]. We found that all PA measures declined during the first lockdown; compliance with current PA recommendations sunk from 38.1% to 30.4% [11].…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…Given these results, findings from the first wave of the pandemic and the ensuing lockdowns are alarming. Numerous studies worldwide and in Germany have documented reduced PA at the level of overall samples [10][11][12]. We found that all PA measures declined during the first lockdown; compliance with current PA recommendations sunk from 38.1% to 30.4% [11].…”
Section: Introductionmentioning
confidence: 54%
“…Numerous studies worldwide and in Germany have documented reduced PA at the level of overall samples [10][11][12]. We found that all PA measures declined during the first lockdown; compliance with current PA recommendations sunk from 38.1% to 30.4% [11]. In contrast to the first lockdown, data on PA during the second lockdown are scarce.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…All questions on PA were posed twice, once relating to conditions prior to lockdown ("normal"), and once relating to lockdown ("lockdown") conditions. Data on habitual PA has been published elsewhere [27].…”
Section: Questionnairementioning
confidence: 99%